2001
DOI: 10.1677/joe.0.1700217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of thyroglobulin domain(s) involved in cell-surface binding and endocytosis

Abstract: Thyroglobulin (Tg) binds to cell surfaces through various binding sites of high, moderate and low affinity. We have previously shown that binding with low to moderate affinity is pH dependent, selective, but not tissue specific. To identify the regions of Tg involved in this cell surface binding, we studied the binding of 125 I-labeled cyanogen bromide peptides from human Tg to cell surfaces of thyroid cells (inside-out follicles) and of CHO cells. Electrophoretic analysis of cell homogenates after binding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…However, it was further demonstrated that this megalin-mediated process resulted in transcytosis of Tg without proteolytic cleavage [29], as observed for antigen processing in the lysosomal compartment. Moreover, a human Tg peptide which is part of the P40 was recently found to bind and enter porcine thyrocytes [30], as described in the present study for the P40 and human thyrocytes.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, it was further demonstrated that this megalin-mediated process resulted in transcytosis of Tg without proteolytic cleavage [29], as observed for antigen processing in the lysosomal compartment. Moreover, a human Tg peptide which is part of the P40 was recently found to bind and enter porcine thyrocytes [30], as described in the present study for the P40 and human thyrocytes.…”
Section: Discussionsupporting
confidence: 72%
“…Albeit not yet defined, it was suggested that this shorter peptide bound and internalized the thyrocytes via a Tg cell-surface component different from megalin, but which occurred widely on various cell-types [30].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to investigate whether and how the difference in the sequence of human Tg and its different heparin-binding capacity affect its binding to HSPGs. Recently, SiffroiFernandez et al (30) provided evidence that the human Tg carboxyl terminal region from Ser2445 to Met2596, comprising the sequence we studied here (Arg2489-Glu2503), is involved in low affinity Tg binding to as yet unidentified molecules on thyroid cell membranes. Based on the results presented here it is worth considering the possibility that binding may be due to HSPGs.…”
Section: Figurementioning
confidence: 83%
“…A commonly used approach to assess the molecular mechanisms of proteins is to establish their functional domains [32,33]. Phylogenetic sequence analysis is a conservation-based method to identify functional domains and related proteins [34,35].…”
Section: Introductionmentioning
confidence: 99%